UNIT 1.23 Overview of Admixture Mapping. (January 2013) - Shriner, Daniel
Abstract: Admixture mapping is a powerful method of gene mapping for diseases or traits that show differential risk by ancestry. Admixture mapping has been applied most often to African Americans who trace ancestry to Europeans and West Africans. Recent developments in admixture mapping include improvements in methods to take advantage of higher densities of genetic variants, as well as extensions to admixed populations with three or more ancestral populations, such as Latino Americans. In this unit, the author outlines the key concepts of admixture mapping. The author describes several approaches for inferring local ancestry and provides strategies for performing admixture mapping depending on the study design. Finally, the author compares and contrasts linkage analysis, association analysis, and admixture mapping, with an emphasis on integrating admixture mapping and association testing. Curr. Protoc. Hum. Genet. 76:1.23.1‐1.23.8. © 2013 by John Wiley & Sons, Inc.